Application of Multiobjective Evolutionary Techniques for Robust Portfolio Optimization - Garcia Rodriguez, Sandra (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2020)
On December 20 of 2012 Sandra García Rodríguez defended his PhD at Carlos III of Madrid (Spain), called: “Application of Multiobjective Techniques for Robust Portfolio Optimization”. This thesis was supervised by Dr. David Quintana Montero and Dr. Inés M. Galván León. The defense was done in a publicly open presentation held at Carlos III University of Madrid. The PhD was approved, with the highest rating Cum Laude, by the examining committee: Dr. José Manuel Molina López, Dr. Antonio Gaspar Lopes da Cunha and Dr. David Camacho Fernández.
Keywords: financial robust portfolio optimization; multiobjective evolutionary algorithms; artificial intelligence; IJIMAI